What threatens public libraries?: The viewpoints of library directors in Sweden. Issue 9 (29th August 2014) - Michnik, Katarina
Abstract : Purpose: This article aims to identify threats perceived by Swedish public library directors as the most prominent. Design/methodology/approach: A web questionnaire was sent to public library directors in all of the Swedish municipalities. The data was analysed using qualitative content analysis. Findings: The findings reveal that the main threat was considered to be the tension between the current activities of the public library and the expectations of the public, or of local decision makers. One reason for the lack of correspondence between activities and expectations is that public library managers regard the expectations on the public library as unrealistic. Another reason is that a lack of resources prevent public library staff from meeting many of these expectations. Public libraries are thus prevented by both ideological and practical barriers in fulfilling expectations. Originality/value: A central issue in current public library research concerns how change in Western society affects public libraries. Many of these studies are either theoretical or based on interviews with politicians. Few researchers investigate how public library directors perceive the situation of public libraries today. Therefore, this article identifies perceptions made by public library directors.